Cardiac Biomarkers and Risk of Incident Heart Failure in Chronic Kidney Disease: The CRIC (Chronic Renal Insufficiency Cohort) Study - Nisha Bansal; Leila Zelnick; Alan Go; Amanda Anderson; Robert Christenson; Rajat Deo; Christopher Defilippi; James Lash; Jiang He; Bonnie Ky; Stephen Seliger; Elsayed Soliman; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Cardiac biomarkers may signal mechanistic pathways involved in heart failure (HF), a leading complication in chronic kidney disease. We tested the associations of NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide), high‐sensitivity troponin T (hsTnT), galectin‐3, growth differentiation factor‐15 (GDF‐15), and soluble ST2 (sST2) with incident HF in chronic kidney disease. Methods and Results We examined adults with chronic kidney disease enrolled in a prospective, multicenter study. All biomarkers were measured at baseline. The primary outcome was incident HF. Secondary outcomes included HF with preserved ejection fraction (EF≥50%) and reduced ejection fraction (EF<50%). Cox models were used to test the association of each cardiac biomarker with HF, adjusting for demographics, kidney function, cardiovascular risk factors, and medication use. Among 3314 participants, all biomarkers, with the exception of galectin‐3, were significantly associated with increased risk of incident HF (hazard ratio per SD higher concentration of log‐transformed biomarker): NT‐proBNP (hazard ratio, 2.07; 95% CI, 1.79–2.39); hsTnT (hazard ratio, 1.38; 95% CI, 1.21–1.56); GDF‐15 (hazard ratio, 1.44; 95% CI, 1.26–1.66) and sST2 (hazard ratio, 1.19; 95% CI, 1.05–1.35). Higher NT‐proBNP, hsTnT, and GDF‐15 were also associated with a greater risk of HF with reduced EF; while higher NT‐proBNP GDF‐15 and sST2 were associated with HF with preserved EF. Galectin‐3 was not associated with either HF with reduced EF or HF with preserved EF. Conclusions In chronic kidney disease, elevations of NT‐proBNP, hsTnT, GDF‐15, sST2 were associated with incident HF. There was a borderline association of galectin‐3 with incident HF. NT‐proBNP and hsTnT were more strongly associated with HF with reduced EF, while the associations of the newer biomarkers GDF‐15 and sST2 were stronger for HF with preserved EF.